The Effects of Three Types of Prophylactic Knee Bracing on Abduction Angle and Abduction Moment of Knee Joint in Foot Rotation Positions during Single Leg Landing in Anterior Cruciate Ligament Injury - Hossein Goldashti; Mansour Eslami; Mohammad Taghipour (Vesnu Publications, 2019)
landing movements. The aim of the present study was to investigate the effect of three preventive knee joints on the variables of abduction angle and abduction moment in three types of single leg landing in healthy young people. Materials and Methods: 15 healthy young people participated in this research. These participants were asked to descend from a platform with height of 30 cm on a force plate in three directions of forward, inward, and outward. Data were recorded during synchronization of camera and force plate, and maximum abduction angle and abduction moment were calculated using MATLAB software. To test research hypotheses, repeated measures ANOVA with a significance level of more than 0.05 was used to evaluate the interactive effect of different types of knee-braces on different landing. Results: The interactive effect of different types of knee-braces on abduction (P = 0.416) and abduction moment (P = 0.442) did not depend on the type of landing. There was no significant difference between different knee braces in knee abduction (P = 0.759) and knee joint abduction moment (P = 0.657). There was significant difference between types of landing in knee abduction angle (P = 0.007) and abduction moment (P = 0.001). Conclusion: Regarding the findings of this research, it seems that between the two variables of landing and knee brace, the first one is more important, and athletes should avoid landing with external leg rotation as far as possible.